1986
DOI: 10.1148/radiology.158.1.3510020
|View full text |Cite
|
Sign up to set email alerts
|

Indwelling ureteral stents: percutaneous management of complications.

Abstract: Complications of indwelling ureteral stents were managed percutaneously in 13 patients. These complications consisted of three fractured, three heavily encrusted, and seven migrated stents. While most ureteral stent malfunctions are routinely managed with retrograde techniques, the percutaneous approach allows effective clinical management in selected cases in which extensive renal stone material or brittle intrarenal stent fragments are present or when previous surgery or ureteral strictures do not permit a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…25 Some investigators have reported high success rates in managing calcified stents using endourologic techniques in a single anesthetic setting 24,26,27 ; however, it is not unusual to need multiple sessions to successfully render the patient stent and stone free, depending on which modalities are used. 15,17,28 Antegrade nephroscopy and ureteroscopy can also serve as alternative means to access the proximal collecting system to perform lithotripsy on calcified ureteral stents. 16 The percutaneous route, as with uncomplicated nephrolithiasis, is the preferred primary approach when stone size is greater than 2 cm and/or if there is associated significant encrustation on the proximal ureteral end of the stent.…”
Section: Evaluation Of Encrusted Stent and Selection Of Extraction Tementioning
confidence: 99%
See 1 more Smart Citation
“…25 Some investigators have reported high success rates in managing calcified stents using endourologic techniques in a single anesthetic setting 24,26,27 ; however, it is not unusual to need multiple sessions to successfully render the patient stent and stone free, depending on which modalities are used. 15,17,28 Antegrade nephroscopy and ureteroscopy can also serve as alternative means to access the proximal collecting system to perform lithotripsy on calcified ureteral stents. 16 The percutaneous route, as with uncomplicated nephrolithiasis, is the preferred primary approach when stone size is greater than 2 cm and/or if there is associated significant encrustation on the proximal ureteral end of the stent.…”
Section: Evaluation Of Encrusted Stent and Selection Of Extraction Tementioning
confidence: 99%
“…16 The percutaneous route, as with uncomplicated nephrolithiasis, is the preferred primary approach when stone size is greater than 2 cm and/or if there is associated significant encrustation on the proximal ureteral end of the stent. 17,18,28 In the case of simultaneous large proximal and distal encrustations, the issue of which encrusted end to address first, proximal or distal, is a matter of preference and severity of stone burden. However, managing the lower coil first transurethrally, placing a ureteral catheter retrograde, and repositioning the patient to the prone position to obtain percutaneous access to manage the upper coil is an efficient and logical approach.…”
Section: Evaluation Of Encrusted Stent and Selection Of Extraction Tementioning
confidence: 99%
“…Without prompt and appropriate management, such complications can be fatal. They can arise in several situations, including in extirpative surgery for malignant pelvic or abdominal disease, with previous vascular reconstruction procedures, and in degenerative iliac artery disease [1,2]. Vein complications involving the ureter are even less common than are arterial complications.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Retrograde retrieval, however, can be difficult or impossible because of proximal migration of the stent, encrustation, previous surgery on the bladder, altered anatomic features of the ureter/vesicoureteric anastomosis, inability to maintain lithotomy position, or enlargement of the prostate. [8] Shin et al . have also elaborated few other reasons for difficult retrograde stent removal including history of surgery resulting in an inaccessible retrograde route, urethral stricture, fragmentation of the proximal stent, and inability to find the ureteral orifice with a cystoscope.…”
Section: Discussionmentioning
confidence: 99%